Determinants of bank profitability in CEE countries: Evidence from GMM panel data estimates - Alexandra Horobet; Magdalena Rădulescu; Lucian Belascu; Sandra Maria Dita (Journal of Risk and Financial Management, 2021)
Given the high resilience of the Central and Eastern Europe (CEE) banking sectors during the last financial crisis and their major role in the CEE region in financing the economy and supporting the high growth rates achieved there, our paper investigates the determinants of banking profitability in the CEE banking sectors based on a Generalized Method of Methods (GMM) approach using data between 2009 and 2018. We have selected determinants from the macroeconomic factors and from the financial-banking specific factors using a two-step GMM method. Our findings demonstrate that unemployment rate, inflation, budget balance, non-governmental credit, non-performing loan rates, concentration rate and capitalization rate negatively impact on the banking profitability in the CEE banking sectors. According to these findings, some policy recommendations were elaborated.
Keywords: 330; bank profitability; Central and Eastern Europe; dynamic panel; financial markets; GMM estimation; macroeconomic conditions